2018
DOI: 10.1039/c8cp06061d
|View full text |Cite
|
Sign up to set email alerts
|

Ion-specificity and surface water dynamics in protein solutions

Abstract: Ion-specific effects at the protein surface are investigated here in light of the changes they infer to surface water dynamics, as observed by 1H NMR relaxation (at 20 MHz). Two well-known proteins, hen egg-white lysozyme (LZM) and bovine serum albumin (BSA), show qualitatively opposite trends in the transverse relaxation rate, R2(1H), along a series of different monovalent salt anions in the solution. Presence of salt ions increases R2(1H) in the case of lysozyme and diminishes it in the case of BSA. The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 79 publications
3
20
0
Order By: Relevance
“…As a direct consequence of the water asymmetry, the anions have a stronger hydration than the cations: (i) since the oxygen atom of water is quite electronegative, it is easier for water to accept a negative charge from the anions than to accept a positive charge from the cations, and (ii) anions interacting with the hydrogen atoms of water can facilitate inter-shell hydrogen bonding between water molecules [ 2 , 60 ]. A number of experimental studies have confirmed that the influence of anions on protein solutions is much greater than the influence of cations [ 56 , 55 ] (even at p H ≫ p I [ 57 ]). When some of the salt anions bind to the protein surface of a net neutral protein molecule ( p H = p I), the effect is the same as when the protein is in a solution with p H slightly above p I ( p H > p I).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a direct consequence of the water asymmetry, the anions have a stronger hydration than the cations: (i) since the oxygen atom of water is quite electronegative, it is easier for water to accept a negative charge from the anions than to accept a positive charge from the cations, and (ii) anions interacting with the hydrogen atoms of water can facilitate inter-shell hydrogen bonding between water molecules [ 2 , 60 ]. A number of experimental studies have confirmed that the influence of anions on protein solutions is much greater than the influence of cations [ 56 , 55 ] (even at p H ≫ p I [ 57 ]). When some of the salt anions bind to the protein surface of a net neutral protein molecule ( p H = p I), the effect is the same as when the protein is in a solution with p H slightly above p I ( p H > p I).…”
Section: Resultsmentioning
confidence: 99%
“…In several of our previous works, we have shown that thermodynamic properties, such as enthalpy changes upon dilution or mixing in polyelectrolyte solutions [ 59 , 62 , 63 , 57 ], or alternatively, cloud-point temperature data for protein solutions [ 28 ] correlate well with hydration properties of low molecular mass salt ions. The correlation of the T c with the Gibbs free energy of hydration, Δ hyd G , of the low molecular mass salt ions used in this work is examined in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The data in Figure 1 are clearly consistent with our previous measurements at a single frequency of 20 MHz, which showed an increased sensitivity of R 2 (transverse NMR relaxation rate), as opposed to R 1 , to the salt specific effects in LZM and BSA solutions. 37 Importantly, the current multi-frequency data incite the development and allow the testing of a multi-scale model of the water dynamics at protein surfaces, in order to explain the protein-specific response in Figure 1. The model considers both long-lived ("embedded") and short-lived ("transiently diffusing") water molecules on the protein surface.…”
Section: Nmrdmentioning
confidence: 99%
“…Torres et al have shown the applicability of this model for RNA, (1) 1∕T 1 = P free ∕T 1,free + P bound ∕ T 1,bound + bound , BSA, and sodium dodecyl sulfate (SDS) micelles that justify it as universal for biomolecules [27]. Similar studies were performed using 14 N, 35 Cl, and 37 Cl nuclei [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 89%